Prevalence of Thyroid Dysfunction among Patients with Chronic Kidney Disease Attending Diagnostic Laboratory Services, Bulawayo, Zimbabwe - Sibanda, Lindwe Angela; Olivier, Sundika Makengo; Yacoubou, Idi Doutchi; Kaka, Aboubacar Katiella; Salissou , Maibouge Tanko Mahamane (Diversity: Disease Preventive of Research Integrity, 2024)
Chronic kidney disease (CKD), can alter thyroid hormone production, distribution, and excretion. Thyroid dysfunctions like hypothyroidism, hyperthyroidism, and euthyroidism are identified in renal failure patients. This study aimed to determine thyroid dysfunction prevalence among CKD patients who attended Diagnostic Laboratory Services in Bulawayo from January to December 2023. The study was analytical cross-sectional and archival data collection methods were to gather information from 118 CKD patients who underwent both thyroid function tests and urea and electrolytes tests. A descriptive and analytical statistic test was used to determine the prevalence of thyroid dysfunction among CKD patients Chi square test was used to test association between thyroid’s dysfunction in CKD setting with various risk factors, P< 0.05 was considered as statistically significant. Thyroid dysfunction (TD) prevalence was 53%, increasing with CKD severity, with stage 3B having a high prevalence of 37%. Major types include subclinical hypothyroidism (11%), overt hypothyroidism (16%), and subclinical hyperthyroidism (4.2%), with 36% of females presenting with thyroid dysfunction as compared to 31% of males. Prevalence of thyroid dysfunction increased with an increase in age Majors risk factor for CKD in TD setting were hypertension, diabetes, and heart failure. In conclusion, there was a high prevalence of thyroid dysfunction (53%) among chronic kidney disease patients.